Synthesis and Spectral Studies of R(2),C(4)-Bis(Tert-Butoxycarbonyl)-C(5)-Hydroxy-T(5)-Methyl-T(3)-Phenyl Cyclohexanone and Their Biological Activity - Sumathi, T.; Anandhan, B.; Sivakumar, P.; Kamatchi, S. (Journal of Scientific Research, 2023)
There are three new t(3)-aryl-r(2),c(4)-bis(tert-butoxycarbonyl)-c(5)-hydroxy-t(5)-methyl- cyclohexanones (1-3) have been synthesized by condensing tert-butyl acetoacetate with different aromatic aldehydes in the presence of methylamine as a stereospecific catalyst. The structures of the products were confirmed by 1H NMR, 13C NMR, and IR spectroscopic techniques. For compound (1), HMBC, HSQC, COSY, NOESY, and Mass spectra of the compounds were studied. Elemental analysis was carried out for all the compounds. In vitro biological applications like anti-inflammatory and antioxidant activities were also performed. The tert-butoxycarbonyl cyclohexanones showed good anti-inflammatory and antioxidant activities, and the percentage of inhibitions is nearer to standard drugs.